Current collapse degradation in GaN High Electron Mobility Transistor by virtual gate. (December 2021) - Godfrey, D.; Nirmal, D.; Arivazhagan, L.; Godwinraj, D.; Mohan Kumar, N.; Chen, Yulin; Yeh, Wenkuan
Abstract: A Virtual Gate model with surface traps at gate edge of drain side is modelled for AlGaN/GaN High Electron Mobility Transistor (HEMT). This model conﬁrms the utility of a Field Plate (FP) enhances sheet carrier density and suppress current collapse. At the gate-edge of drain side, the channel electron density with Field Plate are 2.1 × 10 9 cm −3, 4.68 × 10 9 cm −3 and 8.63 × 10 9 cm −3 for LFP = 0.5 μm, LFP = 1 μm and LFP = 1.5 μm is increased with respect to Length of Field Plate, whereas without the Field Plate shows much lower electron density value of 1.14 × 10 9 cm −3 in the device. The increase of Drain current (Ids ) from 736 mA/mm to 813 mA/mm with the increase in LFP from 0 μm to 1.5 μm is observed for Drain voltage (Vds ) at 40 V. Furthermore, Field Plate shows a great control over electric field and trapped carrier density at gate edge of the device. The formulated model in this paper is correlated-well with the simulation result of AlGaN/GaN HEMT.